New industries and windows of locational opportunity.: A long-term analysis of Belgium - Boschma, Ron A. (ERDKUNDE, 1997)
This article aims to set out a theoretical concept (the Window of Locational Opportunity concept), which provides a particular perspective with respect to the key problem in economic geography of how to explain the location of new industries. This WLO-concept describes the spatial formation of newly emerging industries in terms of indeterminacy, creativity and chance. In short, this theoretical concept holds the view that windows of locational opportunity tend to open up in the event of new industries: these are likely to provide opportunities of industrial development for both leading and backward regions. This is because the spatial formation of new industries during their initial stage of growth takes place rather independently of spatial structures and conditions laid down in the past. The impact of space is believed to be unpredictable and rather weak for several reasons: there is likely to be a poor match with the new requirements of new industries, their creative ability may safeguard their development in unfavourable places, while local conditions favourable to their development are likely to be of a generic nature. Following the principles behind this concept, we present a long-term spatial analysis of Belgium. First, we demonstrate empirically that the industrial history of Belgium in the last two centuries showed that newly emerging industries do not require a particular type of region in order to develop. As expected by the WLO-concept, new industries provide opportunities for both leading regions and lagging regions, and for both old industrial areas and backward regions. Secondly, a more in-depth analysis of a few selected new industries underlined the importance of creativity and chance at their initial stage of development. By doing so, we focus attention on questions whether the spatial formation of new industries goes along with the creation of essential inputs, whether this creative ability of new industries is influenced by particular conditions in the region concerned, and (if so) whether these local conditions can be considered unique to the region(s) concerned. Broadly speaking, this long-term analysis of Belgium provides evidence that some of the new industries emerged quite independently of specific spatial conditions accumulated in the past. Their spatial formation went along with a well-developed ability to generate or attract the required resources. Although this creative capacity could indeed build on particular conditions in the region(s) concerned, these conditions can often be considered to be widely available in space.